Evaluation of mild cognitive impairment subtypes in Parkinson's disease. Issue 6 (7th April 2014) - Cholerton, Brenna A.; Zabetian, Cyrus P.; Wan, Jia Y.; Montine, Thomas J.; Quinn, Joseph F.; Mata, Ignacio F.; Chung, Kathryn A.; Peterson, Amie; Espay, Alberto J.; Revilla, Fredy J.; Devoto, Johnna; Watson, G. Stennis; et al.
ABSTRACT Mild cognitive impairment in Parkinson's disease (PD‐MCI) is common and increases the risk for dementia. Establishing distinct PD‐MCI cognitive subtypes could be valuable for eventually predicting those most likely to convert to dementia. However, the study of PD‐MCI subtypes has not yielded consistent results among cohorts. To determine whether there are distinct cognitive subtypes among participants diagnosed with PD‐MCI in the Pacific Northwest Udall Center Clinical Consortium, we cognitively subtyped 95 patients with PD‐MCI, using the Movement Disorders Society Task Force diagnostic guidelines. Psychometric test scores were then subjected to principle components factor analysis to determine whether similar cognitive subgroups could be identified using statistical methodology. Multiple‐domain PD‐MCI was diagnosed in 95% of the sample, and a range of cognitive impairments were noted. Factor analysis yielded seven factors and demonstrated overlap of phonemic verbal fluency on two factors, as well as the loading of verbal fluency on the same factor as a visuospatial measure; however, these factors did not partition the sample into distinct cognitive subtypes. Separation of cognitive subtypes based on the current PD‐MCI criteria, or via statistical methods, may not provide sufficient information to describe distinct PD groups. Future efforts to validate the PD‐MCI criteria and identify combinations of genetic or other risk factors for cognitive impairment are warranted. © 2014 International Parkinson and Movement Disorder Society